Appealing To The Senses Visually: An Analysis Of Instagram Ads For Kopi Kenangan And Its Influence On Brand Awareness Among Gen Z - Juwita Wirta Sri Depi; Ainal Husna (Asosiasi Dosen Muda Indonesia, 2025)
Instagram has evolved into a dominant visual medium in digital marketing strategies, particularly for reaching Generation Z, who are highly responsive to aesthetic and interactive content. This study aims to analyze how visual design elements in Instagram ads for Kopi Kenangan influence brand awareness among Gen Z. A quantitative approach was used through an online survey of 150 respondents aged 17–25 who are active on Instagram and have seen Kopi Kenangan ads. Data analysis was conducted using Pearson correlation tests and simple linear regression. The results show that visual elements such as dominant colors, consistent typography, narrative caption style, and logo placement significantly affect brand recall and brand recognition. Bright, contrasting colors were found to be most effective in grabbing initial attention, while the consistent use of logos reinforced brand memory over the long term. These findings emphasize the important role of visual communication in building a strong brand image on digital platforms and provide practical implications for small and medium-sized enterprises (SMEs) and the creative industry in designing effective visual content.